2008
DOI: 10.1024/1421-0185.67.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Smiling Episodes and Therapeutic Alliance in a Therapist-Couple Discussion Task

Abstract: We observed mutual smiling episodes (MSEs) during therapist-couple triadic interaction as a key element of affective exchanges that serve to regulate the therapeutic relationship. Based on a functional perspective, we developed a new rating scale, the MSE Coding System (MSE-CS) that allows us to distinguish between four different MSEs, which correspond to four social functions: supporting mutual binding, sharing miseries, repairing, and confronting. MSEs were analyzed in a sample of eight therapist-couple tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Darwiche et al. () found mutual smiling episodes during therapist‐couple triadic interactions to be a key element within the affective exchanges that serve to regulate the therapeutic relationship. Benecke et al.…”
Section: Rhythmic Attunement and Embodied Synchronization In Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Darwiche et al. () found mutual smiling episodes during therapist‐couple triadic interactions to be a key element within the affective exchanges that serve to regulate the therapeutic relationship. Benecke et al.…”
Section: Rhythmic Attunement and Embodied Synchronization In Actionmentioning
confidence: 99%
“…Raingruber (2001) observed that the therapist and the patient tend to synchronize their nonverbal behavior in important moments of therapy, attuning to each other in this way. Darwiche et al (2008) found mutual smiling episodes during therapist-couple triadic interactions to be a key element within the affective exchanges that serve to regulate the therapeutic relationship. Benecke et al (2005) noted a connection between simultaneous smiling in conflict situations and perceived relationship satisfaction.…”
Section: Therapeutic Changes In Relation To Embodied Synchronymentioning
confidence: 99%
“…They observed that clients' experience of the session was related to this synchronicity. Observations of embodied attunement have also been conducted by focusing on the facial expression of emotions during psychotherapy interactions (Bänninger-Huber & Widmer, 1999;Benecke, Peham, & Bänninger-Huber, 2005;Darwiche et al, 2008). Marci, Ham, Moran, and Orr (2007) studied client and therapist dyads and found that client-perceived empathy was connected to good mutual concordance in skin conductance (SC) between the participants.…”
Section: The Present Study Is Part Of a Research Project Called The Rmentioning
confidence: 99%
“…Darwiche et al. () found mutual smiling episodes (MSEs) during therapist‐couple triadic interactions to be a key element within the affective exchanges that serve to regulate the therapeutic relationship. In their MSE Coding System (MSE‐CS), they distinguished between supporting, mutual binding, sharing miseries, repairing, and confronting.…”
Section: Rhythmic Attunement In Psychotherapymentioning
confidence: 99%